An energy efficient weakly programmable MIMO detector architecture - C. Gimmler-Dumont; N. Wehn (Advances in Radio Science, 2013)
Energy efficient processing is mandatory in todays' mobile devices. For the upcoming multiple-antenna systems, algorithmic flexibility enables the dynamic reaction to changing channel conditions. We show that most of the tree search based MIMO detection algorithms are based on the same algorithmic kernels and present a weakly-programmable architecture based on these observations. In this way, the detection algorithm can be chosen and parameterized during runtime according to the current channel conditions and QoS requirements leading to a highly energy efficient implementation. The architecture has been implemented and synthesized on a 65 nm technology, resulting in an area of 0.26 mm2 and a power consumption of only 15 mW.